2019
DOI: 10.1080/03007995.2019.1699517
|View full text |Cite
|
Sign up to set email alerts
|

A survey of care pathway and health-related quality of life impact for children with central precocious puberty

Abstract: Objective: To describe the timeline to diagnosis for children with central precocious puberty (CPP) and evaluate their psychosocial and health-related quality of life (HRQoL). Methods: A cross-sectional survey was used to prospectively collect data from caregivers, recruited via the MAGIC Foundation, of children with CPP. The control (non-CPP) group was recruited from a national panel of parents/caregivers. After completing a screening survey, respondents completed a burden of illness survey. Respondents in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Mothers' anxiety and stress scores decreased significantly after the NSP. As was observed in this study, the literature shows that mothers of daughters with precocious puberty experience anxiety and stress (Klein et al, 2020; Lee & Kim, 2017; Lee et al, 2018; Patel, 2016; Schoelwer et al, 2015). Despite the high rate of anxiety and stress, only one interventional study was found in the literature on mothers' anxiety and stress.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Mothers' anxiety and stress scores decreased significantly after the NSP. As was observed in this study, the literature shows that mothers of daughters with precocious puberty experience anxiety and stress (Klein et al, 2020; Lee & Kim, 2017; Lee et al, 2018; Patel, 2016; Schoelwer et al, 2015). Despite the high rate of anxiety and stress, only one interventional study was found in the literature on mothers' anxiety and stress.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies in the literature suggest that medical treatment may prevent psychosocial problems by stopping the development of physical symptoms in girls with precocious puberty. However, several studies indicated no difference in the groups' posttreatment CBCL 6/18 scores (Klein et al, 2020; Schoelwer et al, 2015, 2017; Wojniusz et al, 2016), whereas others reported a significant increase (Kim & Lee, 2012; Xhrouet‐Heinrichs et al, 1997). Xhrouet‐Heinrichs et al (1997) reported high scores of withdrawal, anxiety/depression, and somatic complaints at the Child Behavior Checklist even 2 years after the start of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puberte prekoks semptomlarının başlaması ile bir çocuk endokrinolojisi birimine sevk ve nihai tedavi arasında beklenenden daha uzun bir gecikme vardır. Bu durum hastalık yükünü arttırmaktadır (29). düşünülmekle birlikte yapılan çalışmalarda tedavi öncesi ve sonrası arasında annelerin anksiyete, stres değerlerinde anlamlı bir değişimin olmadığı ifade edilmiştir (10,33).…”
Section: Puberte Prekoks'un Anne üZerine Etkileriunclassified
“…Boys with early-onset puberty may have behavioral difficulties and poor psychological adjustment ( 9 ), and girls may experience increased stress from early breast development and onset of menses ( 8 ). Indeed, girls who experience early menarche are also at risk of depressive symptoms and anti-social behaviors from adolescence into early-middle adulthood ( 10 ), as well as lower quality of life ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%